PENGELOLAAN PANTAI SAMUDERA INDAH MENURUT FATWA DEWAN SYARIAH NASIONAL-MAJELIS ULAMA TENTANG PEDOMAN PENYELENGGARAAN PARIWISATA BERDASARKAN PRINSIP SYARIAH - Slamet Riyadi; Rusdi Sulaiman; Ari Widiyawati (Al-Aqad, 2024)
This research aims to find out the management at Samudera Indah Beach and study it based on the Fatwa of the National Sharia Council-Majelis Ulama Indonesia No. 108/DSN-MUI/X/2016 concerning Guidelines for Tourism Operations Based on Sharia Principles. Based on the results of observations and interviews, researchers found that: 1) The form of management at Samudera Indah Beach has facilities provided by the manager such as gazebo facilities, halls, parking lots, prayer rooms, lodging/villas, places to relax on the coast, camping sites, public toilets, bathrooms, rinse rooms, canteens, landfills, directions, and lakes for children. For security management, the manager has conducted socialization related to security for visitors, provided parking attendants to guard visitors' vehicles, provided supervisors on the shoreline, loudspeakers to provide appeals when the weather is bad, and a return post for goods if they find items that do not belong to them. 2) The management of Samudera Indah Beach according to the Fatwa of the National Sharia Council-Majelis Ulama Indonesia No. 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles shows the existence of relevant norms and irrelevant norms and norms that have not been fulfilled at Samuderea Indah Beach, Bengkayang Regency. The transaction or contract is in accordance with the provisions of the ijarah contract in the MUI Fatwa.